2012
DOI: 10.1037/a0026663
|View full text |Cite
|
Sign up to set email alerts
|

Attending to religion and spirituality in group counseling: Counselors' perceptions and practices.

Abstract: Although consensus is building that religion and spirituality are important aspects of individual counseling, there has been little exploration of these topics in group counseling. The current online questionnaire study provided a description of how 242 experienced group counselors approach religion and spirituality in group counseling. Interventions that were less active and less directly tied to religious or spiritual practices were viewed as the most appropriate. Spiritual interventions were seen as more ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…The perceived appropriateness of religious and spiritual interventions measure (Comish, Wade, & Post, 2012) was used to assess clients' perceived appropriateness of 14 R/S interventions. Five pairs of interventions comprise 10 of the items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived appropriateness of religious and spiritual interventions measure (Comish, Wade, & Post, 2012) was used to assess clients' perceived appropriateness of 14 R/S interventions. Five pairs of interventions comprise 10 of the items.…”
Section: Methodsmentioning
confidence: 99%
“…The only empirical article that examined R/S in general counseling groups of which we are aware explored the group therapists' perspectives on this issue (Cornish, Wade, & Post, 2012). In this study, 242 experienced group therapists rated the appropriateness and use of religious and spiritual interventions in their group work.…”
Section: Religion and Spirituality In Group Counselingmentioning
confidence: 99%
“…Frazier and Hansen () determined that clinicians' own religious and spiritual identities were associated with the frequency in which they engaged in religious or spiritual behaviors with clients. In addition, Cornish et al () found a significant positive association between counselors' own religious commitment and spirituality and the frequency with which they used religious or spiritual interventions. Therefore, it appears that counselors' religious and spiritual identities may influence the way in which they attend to clients' religion and spirituality in session.…”
Section: Attending To Religion and Spirituality In Counselingmentioning
confidence: 99%
“…Less research has looked at the stereotypes and expectations people hold about spiritual individuals. Some have looked at beliefs about spirituality in relation to something else such as how spirituality can play a role in counseling (Cornish, Wade, & Post 2012;Henriksen, Polonyi, Bornsheuer-Boswell, Greger, & Watts, 2015). Overall, most of the research on stereotypes has focused on who is viewed favorably and who is viewed unfavorably.…”
Section: Religion and Spiritualitymentioning
confidence: 99%